AUDIT STRUKTUR GEDUNG BANK X KOTA BANJARMASIN - Syapril Janizar; Felix Setiawan; Denah Harun Saputra (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2020)
This study aims to ensure that the existing conditions of the structure of the Bank X Building inBanjarmasin City are still able to withstand the burden that occurs and can meet the service periodproperly in accordance with applicable regulatory standards. In this study, structural inspection isdescribed structural inspection, starting from visual inspection, undestructive inspection of buildingstructures by testing the compressive strength of concrete using a Hammer Test, testing the number ofreinforcement, reinforcement distance and a concrete blanket using the Rebar Locator / Cover Meterand verticality checking / building rigidity. In addition, the results of the examination of the structure ofthe building were analyzed by modeling the existing building structure elements using tools or structuralanalysis software. The final result of this study is to provide recommendations for structuralimprovement in accordance with the level of damage that occurs.